Modified material for high-temperature-resistant precoated sand, precoated sand and preparation method of modified material
By effectively combining silica powder and graphite modifiers with resin in coated sand, and leveraging the advantages of Hainan sand and recycled sand, the problem of poor heat resistance of coated sand is solved, achieving improved high-temperature resistance and reduced expansion rate, making it suitable for casting complex and thin-walled parts.
Patent Information
- Application Number
- CN202511182511.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-28
AI Technical Summary
Existing coated sand has poor heat resistance, and is prone to cracking, especially when casting complex or thin-walled castings. It also has poor material compatibility, and the inorganic refractory particles have weak bonding ability with resin, making it unable to effectively resist high-temperature molten metal.
Using silica powder and graphite as modifying materials, silane coupling agents are used to form silanol bonds and π-π stacked bonds with resin. Hainan sand and recycled sand are used as substrates. By utilizing the mechanical sand-adhesive properties of silica powder and the heat resistance properties of graphite, high-temperature resistant coated sand is prepared.
It improves the high-temperature resistance of coated sand, prevents sand adhesion and carburization of castings, is suitable for the production of large cast steel parts, and reduces the sand mold expansion rate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of casting coated sand technology, specifically relating to a modified material for high-temperature resistant coated sand, coated sand, and its preparation method. Background Technology
[0002] Coated sand refers to molding sand or core sand for making cast steel or cast iron molds, with a solid resin film coated on the surface of the sand grains before molding. There are two processes for making coated sand: cold method and hot method. In the cold method, the resin is dissolved in ethanol, and hexamethylenetetramine is added during the sand mixing process so that the two coat the surface of the sand grains. The ethanol evaporates to obtain coated sand. In the hot method, the sand is preheated to a certain temperature, resin is added to melt it, and the mixture is stirred to coat the surface of the sand grains with resin. Hexamethylenetetramine aqueous solution and lubricant are added, and the mixture is cooled, crushed, and sieved to obtain coated sand.
[0003] Coated sand has become increasingly widely used in recent years due to its advantages such as high strength, low gas generation, high dimensional accuracy of castings, smooth surface, and easy storage. However, current coated sand has poor heat resistance, which is particularly evident in its tendency to crack when casting complex structures, especially thin-walled castings, and its poor material compatibility. Therefore, the current approach is to add inorganic high-temperature resistant additives to coated sand to improve its heat resistance.
[0004] CN 104772426A discloses a high-temperature resistant coated sand, comprising raw sand, binder, curing agent, coupling agent, lubricant, and refractory particles. The curing agent accounts for 40-45% of the binder, the coupling agent accounts for 7-8% of the binder, the binder accounts for 9-10% of the raw sand, the wetting agent accounts for 3-5% of the raw sand, and the refractory particles account for 15-18% of the raw sand. By adding refractory particles to the coated sand, the overall fire resistance and structural stability of the coated sand are improved. However, since inorganic refractory particles can only be dispersed in resin through stirring, the bonding ability between the refractory particles and the resin is weak, and it cannot effectively help the sand mold resist high-temperature molten metal during casting. Summary of the Invention
[0005] The purpose of this invention is to provide a modified material for high-temperature resistant coated sand, thereby improving the high-temperature resistance of the coated sand.
[0006] Another objective of this invention is to provide a method for preparing a modified material for high-temperature resistant coated sand, achieving effective bonding with resin.
[0007] Another objective of this invention is to provide a high-temperature resistant coated sand that overcomes the aforementioned technical problems in the prior art.
[0008] Another objective of this invention is to provide a method for preparing high-temperature resistant coated sand, which uses a mixture of Hainan sand and recycled sand as a substrate. This method combines the high-temperature resistance of Hainan sand due to its high silica content with the low expansion performance of recycled sand after calcination, making it suitable for production scenarios such as large cast steel parts.
[0009] Therefore, the technical solution provided by the present invention is as follows:
[0010] A modified material for high-temperature resistant coated sand is composed of the following components in parts by weight: Mixture 1 100-120 parts, Mixture 2 20-30 parts, and the mesh size of the modified material is not greater than 800 mesh.
[0011] The mixture comprises silica powder and silane coupling agent, wherein the mass ratio of silica powder to silane coupling agent is 1000:50~100;
[0012] The mixture two comprises graphite and a coupling agent, wherein the mass ratio of graphite to coupling agent is 1000:100~200.
[0013] Silica powder is used as a heat-resistant auxiliary agent to solve the problem of mechanical sand adhesion. By adding refractory modifiers, it is prevented that the molten metal burns through the resin and penetrates into the sand mold, causing sand adhesion.
[0014] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane or vinyltriethoxysilane.
[0015] The triethoxy group in the silane coupling agent combines with the silicon micropowder to form silanol bonds that bond with inorganic substances.
[0016] Furthermore, the graphite is a mixture of scaly graphite and ochre graphite, with a mass ratio of scaly graphite to ochre graphite of 1:2 to 1:3.
[0017] Earthy graphite has a fine crystal structure, which allows it to be better dispersed and bonded in resin when mixed with coated sand. Scaly graphite has a larger microstructure, which provides better heat resistance. The combination of the two can balance the dispersion and bonding effect and the ability to withstand high temperatures to a certain extent.
[0018] Furthermore, the coupling agent is phenylaminopropyltrimethoxysilane.
[0019] A method for preparing a modified material for high-temperature resistant coated sand includes the following steps:
[0020] Step 1) Put the prescribed amount of silicon micro powder into a mixer and stir at high speed. While stirring, spray the prescribed amount of silane coupling agent into the mixer using a nozzle. Spray for 30-40 minutes. Then continue stirring for 30-40 minutes. Dry the resulting mixture and ball mill it to obtain mixture one.
[0021] Step 2) Put the prescribed amount of graphite into a mixer and stir while spraying in the coupling agent. After mixing evenly, dry and ball mill to obtain mixture two.
[0022] Step 3) Mix the mixtures 1 and 2 according to the formula for 1 to 1.5 hours, and then air classify to obtain powder with a mesh size of less than 800, which is the modified material.
[0023] Silica powder and graphite particles are small and have a large surface area. After the addition of coupling agents, they may stick together. Ball milling can not only ensure that they are mixed more evenly with the coupling agent, but also restore the fine particle state, so that they can better combine with the resin in the future.
[0024] A high-temperature resistant coated sand comprises the following components in parts by weight: 3-5 parts of a modifier for high-temperature resistant coated sand, 1000 parts of mixed sand, 25-30 parts of binder, 11-14 parts of curing agent, and 1.8-2.4 parts of lubricant.
[0025] Furthermore, the mixed sand is a mixture of Hainan sand and recycled sand, with a mass ratio of Hainan sand to recycled sand of 1:1 to 2:1, and the silica content of the Hainan sand is above 99%.
[0026] Recycled sand undergoes a high-temperature phase transformation after repeated casting and regeneration at high temperatures, resulting in sand molds with lower expansion rates.
[0027] Furthermore, the adhesive is a phenolic resin.
[0028] Furthermore, the curing agent is hexamethylenetetramine, and the lubricant is calcium stearate.
[0029] A method for preparing high-temperature resistant coated sand involves heating a mixture of sand in a specified amount to 130-140°C, adding a binder in a specified amount and mixing evenly, then adding a modifier in a specified amount while stirring, then adding a curing agent in a specified amount while stirring to remove internal moisture, and finally adding a lubricant in a specified amount to obtain coated sand.
[0030] The beneficial effects of this invention are as follows:
[0031] The modified material for high-temperature resistant coated sand provided by this invention combines the triethoxy group in the silane coupling agent with the silica powder to form silanol bonds that bond with inorganic substances; the amino and vinyl groups combine with the resin through nitrogen bonds and methine bonds; the benzene ring in phenylaminopropyltrimethoxysilane achieves physical adsorption with the graphite sheets through π-π stacking, and the amino and epoxy groups react with the phenolic resin to achieve coupling, thereby improving the effective combination of the high-temperature resistant modified material and the resin, improving the high-temperature resistance of the product, and preventing sand adhesion and carburization of castings.
[0032] The modified material preparation method of this invention utilizes ball milling. This prevents uneven mixing caused by the adhesion of silicon micropowder / graphite to the coupling agent. Furthermore, ball milling maintains a fine particle state after mixing, ensuring better bonding with the resin. This invention leverages the fine crystal structure of earthy graphite, which allows for better dispersion and bonding in the resin during coating sand mixing. The larger microstructure of scaly graphite provides better heat resistance. The combined use of both methods achieves a balanced dispersion and bonding effect, as well as improved high-temperature resistance.
[0033] The high-temperature resistant coated sand of this invention uses a mixture of Hainan sand and recycled sand as the base material, which takes into account the high temperature resistance brought by the high silica content of Hainan sand and the low expansion performance of recycled sand after calcination, making it suitable for production scenarios such as large cast steel parts. Detailed Implementation
[0034] The following specific embodiments illustrate the implementation of the invention. Those skilled in the art can easily understand other advantages and effects of the invention from the content disclosed in this specification.
[0035] Exemplary embodiments of the invention are now described; however, the invention may be embodied in many different forms and is not limited to the embodiments described herein. These embodiments are provided to fully and completely disclose the invention and to fully convey its scope to those skilled in the art. The terminology used in the exemplary embodiments is not intended to limit the invention.
[0036] Unless otherwise stated, the terms used herein (including technical terms) have their common meaning as understood by one of ordinary skill in the art. Furthermore, it is understood that terms defined in commonly used dictionaries should be understood to have a meaning consistent with the context of their relevant field, and not to be interpreted as having an idealized or overly formal meaning.
[0037] Example 1
[0038] 1. Preparation of modified materials for high-temperature resistant coated sand:
[0039] Step 1) Put 1000g of silicon micro powder into a mixer and stir at high speed. While stirring, spray 50g of silane coupling agent into the mixture using a nozzle. Spraying is completed in 30 minutes. Then continue stirring for 40 minutes. After drying the mixture, ball mill it to obtain mixture one.
[0040] Step 2) Put 1000g of graphite into a mixer and stir. While stirring, spray in 200g of phenylaminopropyltrimethoxysilane coupling agent. After mixing evenly, dry and ball mill to obtain mixture two.
[0041] Step 3) Mix 100g of Mixture 1 and 30g of Mixture 2 for 1 hour, and then air classify to obtain powder with a mesh size of less than 800, which is the modified material.
[0042] The alkyl coupling agent is γ-aminopropyltriethoxysilane. The graphite is a mixture of scaly graphite and amorphous graphite, with a mass ratio of scaly graphite:amorphous graphite = 1:2.5. The silica powder contains more than 98% SiO2. The curing agent is hexamethylenetetramine, and the lubricant is calcium stearate.
[0043] This invention utilizes the fine crystal structure of earthy graphite, which allows it to be better dispersed and bonded in resin during the coating sand mixing process. The larger microstructure of scaly graphite provides better heat resistance. The combination of the two can balance the dispersion and bonding effect and the ability to withstand high temperatures to a certain extent.
[0044] The modified material preparation method employs ball milling and air classification. This prevents uneven mixing caused by the adhesion of silicon micropowder / graphite to the coupling agent. Furthermore, ball milling maintains a fine particle state after mixing, ensuring better bonding with the resin. This invention utilizes the fine crystal structure of earthy graphite, which allows for better dispersion and bonding in the resin during coating sand mixing. The larger microstructure of scaly graphite provides better heat resistance. The combined use of both methods achieves a balance in dispersion, bonding, and high-temperature resistance.
[0045] 2. Preparation of high-temperature coated sand:
[0046] Hainan sand and recycled sand are mixed in a 1:1 mass ratio to obtain mixed sand. Then, 1000g of mixed sand is heated to 130℃ and 30g of phenolic resin binder is added and mixed evenly. Then, 5g of modified material is added while stirring, followed by 12g of curing agent while stirring and extracting the moisture inside the mixer. Finally, 1.8g of lubricant is added to obtain coated sand.
[0047] Recycled sand undergoes a high-temperature phase transformation through repeated casting and regeneration at high temperatures, resulting in sand molds with lower expansion rates. This invention uses a mixture of Hainan sand and recycled sand as the base material, combining the high-temperature resistance of Hainan sand due to its high silica content with the low expansion properties of recycled sand after calcination. This makes it suitable for production scenarios such as large cast steel parts.
[0048] Example 2
[0049] 1. Preparation of modified materials for high-temperature resistant coated sand:
[0050] Step 1) Put 1000g of silicon micro powder into a mixer and stir at high speed. While stirring, spray 70g of silane coupling agent into the mixture using a nozzle. Spraying is completed in 40 minutes. Then continue stirring for 40 minutes. After drying the mixture, ball mill it to obtain mixture one.
[0051] Step 2) Put 1000g of graphite into a mixer and stir. While stirring, spray in 150g of phenylaminopropyltrimethoxysilane coupling agent. After mixing evenly, dry and ball mill to obtain mixture two.
[0052] Step 3) Mix 110g of Mixture 1 and 25g of Mixture 2 for 1 hour, and then air classify to obtain powder with a mesh size of less than 800, which is the modified material.
[0053] The alkyl coupling agent is vinyltriethoxysilane. The graphite is a mixture of scaly graphite and amorphous graphite, with a mass ratio of scaly graphite:amorphous graphite = 1:2. The silica powder contains more than 98% SiO2.
[0054] 2. Preparation of high-temperature coated sand:
[0055] Hainan sand and recycled sand were mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 140℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of modified material was added while stirring, followed by 11g of curing agent while stirring and extracting the moisture inside the mixer. Finally, 2.4g of lubricant was added to obtain coated sand.
[0056] Example 3
[0057] 1. Preparation of modified materials for high-temperature resistant coated sand:
[0058] Step 1) Put 1000g of silicon micro powder into a mixer and stir at high speed. While stirring, spray 100g of silane coupling agent into the mixture using a nozzle. Spraying is completed in 40 minutes. Then continue stirring for 30 minutes. After drying the mixture, ball mill it to obtain mixture one.
[0059] Step 2) Put 1000g of graphite into a mixer and stir. While stirring, spray in 100g of phenylaminopropyltrimethoxysilane coupling agent. After mixing evenly, dry and ball mill to obtain mixture two.
[0060] Step 3) Mix 120g of Mixture 1 and 20g of Mixture 2 for 1 hour, and then air classify to obtain powder with a mesh size of less than 800, which is the modified material.
[0061] The alkyl coupling agent is vinyltriethoxysilane. The graphite is a mixture of scaly graphite and amorphous graphite, with a mass ratio of scaly graphite:amorphous graphite = 1:3. The silica powder contains more than 98% SiO2.
[0062] 2. Preparation of high-temperature coated sand:
[0063] Hainan sand and recycled sand were mixed in a mass ratio of 2:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 130℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of modified material was added while stirring, followed by 14g of curing agent while stirring and extracting the moisture inside the mixer. Finally, 2.1g of lubricant was added to obtain coated sand.
[0064] Comparative Example 1
[0065] 1. Preparation of modified silica powder:
[0066] 1000g of silicon micro powder was placed in a mixer and stirred at high speed. While stirring, 100g of silane coupling agent was sprayed in through a nozzle. The spraying was completed in 40 minutes. Then, stirring was continued for another 30 minutes. The resulting mixture was dried and ball-milled to obtain modified silicon micro powder.
[0067] The SiO2 content in the silicon micropowder is over 98%.
[0068] 2. Preparation of high-temperature coated sand:
[0069] Hainan sand and recycled sand were mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 140℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of modified silica powder was added while stirring, followed by 11g of curing agent. While stirring, the moisture inside the mixer was extracted. Finally, 2.4g of lubricant was added to obtain coated sand.
[0070] Comparative Example 2
[0071] 1. Modified graphite:
[0072] 1000g of graphite was placed in a mixer and stirred. While stirring, 100g of phenylaminopropyltrimethoxysilane coupling agent was sprayed in. After mixing evenly, the mixture was dried and ball-milled to obtain modified graphite.
[0073] The graphite is a mixture of scaly graphite and terreusable graphite, with a mass ratio of scaly graphite to terreusable graphite of 1:2.
[0074] 2. Preparation of high-temperature coated sand:
[0075] Hainan sand and recycled sand were mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 140℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of modified graphite was added while stirring, followed by 11g of curing agent while stirring and extracting moisture from the inside of the mixer. Finally, 2.4g of lubricant was added to obtain coated sand.
[0076] Comparative Example 3
[0077] Preparation of high-temperature coated sand:
[0078] Hainan sand and recycled sand were mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 140℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of silica powder was added while stirring, followed by 11g of curing agent. While stirring, the moisture inside the mixer was extracted. Finally, 2.4g of lubricant was added to obtain coated sand.
[0079] The SiO2 content in the silicon micropowder is over 98%.
[0080] Comparative Example 4
[0081] Hainan sand and recycled sand were mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand was heated to 140℃ and 30g of phenolic resin binder was added and mixed evenly. Then, 5g of graphite was added while stirring, followed by 11g of curing agent while stirring and extracting the moisture inside the mixer. Finally, 2.4g of lubricant was added to obtain coated sand.
[0082] The graphite is a mixture of scaly graphite and terreusable graphite, with a mass ratio of scaly graphite to terreusable graphite of 1:2.
[0083] Comparative Example 5
[0084] Hainan sand and recycled sand are mixed at a mass ratio of 1.5:1 to obtain mixed sand. Then, 1000g of mixed sand is heated to 140℃ and 30g of phenolic resin binder is added and mixed evenly. Then, 11g of curing agent is added while stirring and the moisture inside the mixer is extracted. Finally, 2.4g of lubricant is added to obtain coated sand.
[0085] To further illustrate the effects of the present invention, the flexural strength, tensile strength, high-temperature resistance time, and expansion rate of Examples 1, 2, 3, Comparative Example 1 (modified silicon micropowder), Comparative Example 2 (modified graphite), Comparative Example 3 (no modified material, added silicon micropowder), Comparative Example 4 (no modified material, added graphite), and Comparative Example 5 (no additives) were tested respectively. The test results are shown in Table 1.
[0086] I. Bending strength and tensile strength
[0087] See national standard JB-T8583-2008 Coated sand for foundry.
[0088] II. High Temperature Resistance Time
[0089] The cylindrical sample was placed at a high temperature of 1000℃ and subjected to a constant load of 2kg to test its collapse time.
[0090] III. Expansion Rate
[0091] Measurement using the push rod method:
[0092] Install the specimen: Place the cylindrical specimen into the specimen holder and ensure it is secure. Remove contaminants from the holder system and the specimen surface.
[0093] Apply load: Carefully push the push rod to the top of the specimen and apply a load of 0.1N to 1N.
[0094] Heating process: The temperature is controlled by a temperature control device to rise to 1000℃ at a rate not exceeding 5℃ / min.
[0095] Expansion measurement: Record the displacement change of the push rod during the heating process, and measure the expansion rate by the lifting height.
[0096] Table 1. Test results of the examples and comparative examples
[0097]
[0098] As shown in Table 1, the flexural strength and tensile strength of Examples 1-3 of this invention are higher than those of Comparative Examples 1-5, and their high-temperature resistance time is significantly longer than that of the comparative examples. A longer high-temperature resistance time indicates better high-temperature resistance. This is because Comparative Example 1 uses only modified silica powder, and Comparative Example 2 uses only modified graphite. In contrast, this invention utilizes the synergistic effect of modified silica powder and modified graphite: the triethoxy group in the silane coupling agent combines with the silica powder to form silanol bonds that bond with inorganic substances; the amino and vinyl groups combine with the resin through nitrogen bonds and methine bonds; the benzene ring in phenylaminopropyltrimethoxysilane achieves physical adsorption with the graphite sheets through π-π stacking, and the amino and epoxy groups react with the phenolic resin to achieve coupling, thereby improving the effective bonding between the high-temperature resistant modified material and the resin, enhancing the high-temperature resistance of the product, and preventing sand adhesion and carburization in castings.
[0099] Compared with the present invention, Comparative Examples 3 and 4 belong to the traditional high-temperature resistant coated sand production method. In this method, inorganic high-temperature resistant additives can only be dispersed in the resin by stirring. The additives have a weak bonding ability with the resin and cannot effectively help the sand mold resist high-temperature molten metal during casting.
[0100] Using a mixture of Hainan sand and recycled sand as the base material balances the high-temperature resistance of Hainan sand due to its high silica content with the low expansion properties of recycled sand after calcination. In Example 1, the recycled sand content is higher than in the other two examples and the comparative example, while in Example 3, the recycled sand content is the lowest. Because the recycled sand undergoes repeated casting and high-temperature regeneration, it has undergone a high-temperature phase transformation, resulting in a lower expansion rate for the sand molds made from it. Therefore, Example 1 has the lowest expansion rate, and Example 3 has the highest.
[0101] The examples above are merely illustrative of the invention and do not constitute a limitation on the scope of protection of the invention. Any design that is the same as or similar to the invention falls within the scope of protection of the invention.
Claims
1. A modified material for high-temperature resistant coated sand, characterized in that: It consists of the following components in parts by weight: Mixture 1 100-120 parts, Mixture 2 20-30 parts, and the mesh size of the modified material is not greater than 800 mesh; The mixture comprises silica powder and silane coupling agent, wherein the mass ratio of silica powder to silane coupling agent is 1000:50~100; The mixture two comprises graphite and a coupling agent, wherein the mass ratio of graphite to coupling agent is 1000:100~200.
2. The modified material for high-temperature resistant coated sand according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane or vinyltriethoxysilane.
3. The modified material for high-temperature resistant coated sand according to claim 1, characterized in that: The graphite is a mixture of scaly graphite and terreusable graphite, with a mass ratio of scaly graphite to terreusable graphite of 1:2 to 1:
3.
4. The modified material for high-temperature resistant coated sand according to claim 1, characterized in that: The coupling agent is phenylaminopropyltrimethoxysilane.
5. A method for preparing a modified material for high-temperature resistant coated sand as described in any one of claims 1-4, characterized in that: Includes the following steps: Step 1) Put the prescribed amount of silicon micro powder into a mixer and stir at high speed. While stirring, spray the prescribed amount of silane coupling agent into the mixer using a nozzle. Spray for 30-40 minutes. Then continue stirring for 30-40 minutes. Dry the resulting mixture and ball mill it to obtain mixture one. Step 2) Put the prescribed amount of graphite into a mixer and stir while spraying in the coupling agent. After mixing evenly, dry and ball mill to obtain mixture two. Step 3) Mix the mixture one and mixture two according to the formula for 1 to 1.5 hours, and then air classify to obtain powder with a mesh size of less than 800, which is the modified material.
6. A high-temperature resistant coated sand, characterized in that: The product comprises the following components in parts by weight: 3-5 parts of the modified material for high-temperature coated sand as described in any one of claims 1-4, 1000 parts of mixed sand, 25-30 parts of binder, 11-14 parts of curing agent, and 1.8-2.4 parts of lubricant.
7. The high-temperature resistant coated sand according to claim 6, characterized in that: The mixed sand is a mixture of Hainan sand and recycled sand, with a mass ratio of Hainan sand to recycled sand of 1:1 to 2:1, and the silica content of the Hainan sand is above 99%.
8. The high-temperature resistant coated sand according to claim 6, characterized in that: The adhesive is phenolic resin.
9. The high-temperature resistant coated sand according to claim 6, characterized in that: The curing agent is hexamethylenetetramine, and the lubricant is calcium stearate.
10. A method for preparing high-temperature resistant coated sand as described in any one of claims 6 to 9, characterized in that: Heat the mixed sand according to the formula to 130-140℃, add the binder according to the formula and mix evenly. Then, while stirring, add the modifier according to the formula, then add the curing agent according to the formula and extract the internal moisture while stirring. Finally, add the lubricant according to the formula to obtain the coated sand.
Citation Information
Patent Citations
High temperature-resistant precoated sand
CN104772426A